TANTANGAN STATUS HUKUM ANAK PASCA PERCERAIAN: PERBANDINGAN MAQASHID SYARIAH DAN HUKUM NASIONAL: status hukum anak, perceraian, maqashid syariah, dan hukum nasional - Irsul, Isma; Safriani, Laela (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This article aims to understand the challenges of children's legal status after divorce. The method used in this research is qualitative descriptive, which examines the review from the perspective of maqashid sharia and national law. Humans cannot live by themselves. Humans require assistance from others to fulfill their needs in life. As explained in Surah Ar-Rum verse 21, 'Allah has created humans with their pairs so that they may live in tranquility.'